The challenges in employing digital marketing as a tool for improving sales at selected retail stores in the transkei region - Guzana, Mpumzi; Msosa, Steven Kayambazinthu (Eureka, Social and Humanities (Online), 2022)
During the last decade, the internet has introduced the information age and electronic commerce (e-Commerce) to millions of individuals worldwide, even those living in rural places, thus providing companies with an alternative platform for customer contact than brick-and-mortar stores. Therefore, businesses must alter their conventional marketing techniques and develop new approaches to engage consumers on the platforms where they want to connect and make purchases. This study assessed the perceived challenges in using Digital Marketing to boost sales at retail stores in the Transkei region. A qualitative and exploratory research design was used to collect data from store managers through face-to-face interviews. A non-probability sampling technique, known as purposive sampling, was employed to identify 14 store managers based on their knowledge of the subject matter. The findings of this study show that several factors, such as government legislation [the Protection of Personal Information (POPI) Act of 2016], which states that customers cannot be contacted without their express consent; customers' perceptions; poor connectivity in rural areas; costs and angry customer responses are some of the retailers'challenges in employing Digital Marketing. This research could assist the management of retail stores to comprehend the company's challenges and facilitate the implementation of Digital Marketing initiatives to improve service quality, especially during this period of the Covid-19 pandemic. This study has contributed to the Digital Marketing literature in developing countries and laid the groundwork for future research.